2013
DOI: 10.1108/nlw-04-2013-0036
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of liaison consultations: using reflection to understand information-seeking behavior

Abstract: Users who downloaded this article also downloaded: (2013),"Students' need for cognition affects their information seeking behavior", New Library World, Vol. 114 Iss 11/12 pp. 542-549 http://dx.(2013),"Patterns of graduate students' information seeking behavior: a meta-synthesis of the literature", Journal of Documentation, Vol. 69 Iss 2 pp. 243-274 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The finding that students mostly use Wikipedia and similar sources is consistent with the results of He et al (2012), Johnson et al (2008), Kim (2011), O'Farrell and Bates (2009), and Suarez (2013. Propensity of Croatian students to use online encyclopedias and dictionaries was also observed by Faletar Tanackovic et al (2012), Hebrang Grgić and Miočić (2012), and Špiranec et al (2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The finding that students mostly use Wikipedia and similar sources is consistent with the results of He et al (2012), Johnson et al (2008), Kim (2011), O'Farrell and Bates (2009), and Suarez (2013. Propensity of Croatian students to use online encyclopedias and dictionaries was also observed by Faletar Tanackovic et al (2012), Hebrang Grgić and Miočić (2012), and Špiranec et al (2008).…”
Section: Discussionsupporting
confidence: 90%
“…This is confirmed by the fact that ejournals and e-books, especially in the last few years, belong to the most popular forms of electronic resources among students (Arya & Talukdar, 2010;Hernon, Hopper, Leach, Saunders, & Zhang, 2007;Kandpal, Rawat, & Vithal, 2013;Nicholas et al, 2008;O'Farrell & Bates, 2009;Padmamma, Sathish, & Walmiki, 2013;Pandita, 2012;Suarez, 2013). However, the intensity of use of these resources varies considerably.…”
Section: Literature Reviewmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition to quantitative metrics, qualitative research methods such as questionnaires (Butler & Byrd, 2016), interviews (Rogers & Carrier, 2017), focus groups (Watts & Mahfood, 2015), and analyses of librarians' consultation notes (Suarez, 2013) provide valuable insights into what students learn during consultation sessions. Studies have found that confusion about library terminology can impede student learning (Butler & Byrd, 2016), but that students value the individualized attention from in-depth engagement with the librarian, as well as the librarians' perceived subject expertise (Rogers & Carrier, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relatedly, students who participate in consultations have reported a higher degree of confidence in their research abilities, believing that their research has become more efficient and feeling that they have developed good relationships with the librarian as an educator (Watts & Mahfood, 2015). However, others have found that students tend to overestimate their information-seeking abilities even when they still struggle to develop search strategies or generate keywords beyond those that are laid out in the assignment prompt (Suarez, 2013). In this manner, students in research consultations appear to evince the Dunning-Kruger effect, the cognitive bias whereby people are unable to recognize their own incompetence (Suarez, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%